UJI DAYA HAMBAT EKSTRAK DAUN SIRIH HUTAN (Piper aduncum L.) TERHADAP PERTUMBUHAN BAKTERI Staphylococcus aureus DAN Escherichia coli - Is Patuh Hallianah; Orryani Lambui; Ramadanil Ramadanil (Biocelebes, 2019)
Research about the inhibition test of leaf extract of Piper aduncum L.  on the growth of Staphylococcus aureus and Escherichia coli have been conducted during period of July to December 2016. The aim of this research was to study the effectiveness of leaf extract Piper aduncum L. in inhibition  of S. aureus and E. coli. The extraction method used in the study was method maceration, meanwhile bioassay of extract on the bacteria. by disc diffusion method. The research was design by Completely Randomize Design (CDR) with 5 treatments and 3 replications. The treatments were leaf extract concentration 10%, 30% and 60%.  Positive control Amoxicillin 3% and negative control aquadest. The result showed that leaf extract of Piper aduncum L. had  inhibition effect to the growth of bacterias. The extract concentrate 60% produced the biggest inhibition zone for both S. aureus and E. coli 14 mm. Phytochemical analyses has showed that leaf extract of Piper aduncum L. contained compounds flavonoids, tannins, saponins and alkaloids.UJI DAYA HAMBAT EKSTRAK DAUN SIRIH HUTAN (Piper aduncum L.) TERHADAP PERTUMBUHAN BAKTERI Staphylococcus aureus DAN Escherichia coli